Enterotype-Specific Effects of Red Beetroot (Beta vulgaris L.) Powder and Betanin on Human Gut Microbiota: A Preliminary Study Based on In Vitro Fecal Fermentation Model - Gwang-Pyo Ko; Hyejun Jo; Jungman Kim; Jeong Seon Kim; Kyung-Hwan Boo; Chang Sook Kim (Life)
Red beetroots, rich in betanin, may act as prebiotics and impact gut microbiota. Because the human gut microbiota is unique to each person, the effectiveness of prebiotics varies with the enterotype. In this study, we hypothesized that the effects of red beetroot powder (RP) and betanin pigment (BP) would differ depending on the enterotype. Fecal samples from 30 subjects were analyzed and categorized into three enterotypes: Phocaeicola, Prevotella, and Bifidobacterium. Feces were collected from one representative subject from each enterotype cluster for fermentation. Results showed that RP and BP affected microbiota composition and short-chain fatty acid (SCFA) production differently across enterotypes. The Bifidobacterium cluster showed significantly reduced alpha diversity, with the direction of change in the gut microbiota composition being different from that of other subjects. Additionally, SCFAs significantly increased, with the highest increase in the Bifidobacterium cluster. In this cluster, metabolic pathways related to SCFAs (i.e., starch and sucrose metabolism and glycolysis/gluconeogenesis) were altered. Conversely, Prevotella-dominant feces exhibited fewer changes in SCFAs and a lower increase in Bifidobacterium abundance than the others. These findings highlight that RP and BP elicit enterotype-specific responses in the gut microbiota composition and SCFA production, emphasizing the importance of enterotypes in personalized nutrition.